Comparación de la distorsión geométrica lineal de la telerradiografía digital con la telerradiografía convencional en cráneos humanos - Grández Molina, Madeleine Alessandra (2014)
The lateral cephalometric radiography is an essential tool in clinical practice, especially in the area of orthodontics, allows measurements to investigate the development and growth of the facial skeleton , aiding in the diagnosis and treatment plan for each patient. The first type of radiography was the conventional were used and the development of technology has evolved to be digital . The purpose of this study was to compare the geometric distortion of digital lateral cephalometric with conventional cephalometric in human cadaver skulls . The sample was taken for convenience and was composed of 21 human cadavers dry skulls, three markers were placed on each skull lead. The first marker was at the level of the junction of the sutures sphenofrontal, coronal , flaky and sphenosquamosa and parallel to the Frankfort plane . The second one below the frontozygomatic suture and the last at the branch level of the jaw and positioned in the concave part of the line above and parallel to the Frankfort plane . No significant differences were found when comparing the measurements of conventional and digital plates in the upper and middle third, but when the last third was analyzed differences were found between conventional and digital images . All the images presented distortion when they were compared with the gold standard.